Social–ecological heritage and the conservation of Mediterranean landscapes under global change. A case study in Olzinelles (Catalonia) - Otero, Iago; Boada, Martí; Tàbara, Joan David (Land Use Policy, 2013)
Both biological and cultural diversities seem to be diminishing together along with the progressive interconnection of peoples and ecosystems of the earth under the rules and dynamics of global markets. This has led some conservationists and social scientists to highlight the need for enhanced knowledge on the complex interrelationships between cultural and biological diversities if successful conservation strategies are to be achieved. In this work we show how the long-term coevolution between peasants and their environment sustained habitats and species that are now declining along with rural exodus in a mountainous area of the Mediterranean, a region where the maintenance of diverse landscapes is very much related to the presence of traditional rural activities. We provide an account of agrosilvopastoral practices once performed by the local peasant community and show their embeddedness in a particular set of institutions and worldview within an adaptive social–ecological system. We argue that such practices constitute an essential social–ecological heritage entailing valuable insights for the conservation of Mediterranean landscapes under conditions of global change.
Keywords: Biodiversity; conservation; Cultural diversity; Mediterranean; Social–ecological heritage